(untitled) (Texas Journal of Multidisciplinary Studies, 2021)
Pumping stations are used to irrigate about 78% of irrigated lands in the country with the help of mechanical pumping systems. The construction and reconstruction of new pumping stations, the implementation of comprehensive measures for the quality of repair work and the introduction of new technologies will ensure a guaranteed supply of water for crops. Mandatory shutdowns of pumping stations lead to untimely water supply and, as a result, reduced crop yields. Research and monitoring at the auxiliary pumping station revealed that contamination of the filter system installed in the technical water supply system was one of the main reasons for the forced shutdown of pumping equipment. Therefore, research on improving the technical water supply system for pumping equipment has become an urgent problem.